Islamic-Based Development Concepts: A Research Review - Alwyni, Farouk Abdullah (Journal of Applied Business and Economics, 2022)
The study of Islam in regard to economics began gaining ground around the mid-twentieth century. However, the study of Islamic economics did not really address the developmental challenges facing many Muslim countries and was considered too technical and heavily influenced by neo-classical economics. Issues of development and how a nation can succeed in its development efforts need also to include disciplines other than economics. Hence, this study aims to review previous research related to the relation between religion and development generally, and Islamic-based development concepts in particular. The research methodology applied will be based strictly on past research on these subjects as follows: (i) theology in the form of religion has played an influential role in nations’ capacity building; (ii) there are concerns that the present dominant approach of economics leads to disparity of income and environmental degradation; and (iii) Islamic-based development concepts are expected to present an alternative and, at the same time, correct the perceived lack of substance in the present application of Islamic banking, finance, and economics.